Peran Guru Pendidikan Agama Islam Dalam Menangani Perundungan Digital Pada Remaja - Amin, M. Nasikhul; Fadhilah, Iman; Husna, Akhsanul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research discusses the role of Islamic Religious Education (PAI) teachers in dealing with digital bullying among teenagers in private Madrasah Aliyah. Digital bullying is a social problem that is becoming increasingly prominent along with the intensity of digital media use among teenagers. This research aims to analyze the forms of digital bullying that occur as well as the role and strategies of PAI teachers in preventing and handling it. This research uses a qualitative approach with the type of field research. The research results show that PAI teachers have a strategic role through internalizing moral values in learning, developing students' morals, as well as persuasive and educational approaches in handling digital bullying cases. This research contributes to the development of Islamic Religious Education studies that are responsive to the challenges of the digital era, especially in the context of secondary education.